SLOVAK AS A FOREIGN LANGUAGE FOR THE FIRST-YEAR BACHELOR STUDENTS - Marta Gluchmanova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2022)
Every year, more and more foreign students are enrolled at the Faculty of Manufacturing Technologies in Prešov of the Technical University in Kosice. For this reason, Slovak Language for Foreign Students was introduced as a compulsory subject in the 1st year of bachelor's study. The purpose of the paper was to emphasize the teaching of Slovak as a foreign language and thus help to overcome the problems of foreign students in studying professional subjects. The aim is to provide them with suitable tailor-made study material within the blended form of teaching. Slovak language teachers at the Department of Social Sciences and Humanities used mixed innovative methods and forms of study and tried to increase the language and communication skills of students. The paper compares the results of e-exercises and the final e-test of 140 foreign students from different study programmes in the first year of their bachelor study in the winter semester 2021. Slovak language teachers were able to identify students' strengths and weaknesses based on the results of experimental research. Elimination of the most frequent mistakes will help students to increase the level of technical Slovak language, which they can apply during the study of professional subjects and in future practice in Slovak companies. The university-wide Moodle platform was used for blended learning in teaching Slovak as a foreign language at the Faculty.